Sanguinarine Inhibits the 2-Ketogluconate Pathway of Glucose Utilization in Pseudomonas aeruginosa - Falchi, Federica A.; Borlotti, Giorgia; Ferretti, Francesco; Pellegrino, Gianvito; Raneri, Matteo; Schiavoni, Marco; Caselli, Alessandro; Briani, Federica (Frontiers in Microbiology, 2021)
Interfering with the ability of pathogenic bacteria to import glucose may represent a new promising antibacterial strategy, especially for the treatment of infections occurring in diabetic and other hyperglycemic patients. Such patients are particularly susceptible to infections caused by a variety of bacteria, among which opportunistic pathogens like Pseudomonas aeruginosa. In P. aeruginosa, glucose can be directly imported into the cytoplasm or after its periplasmic oxidation into gluconate and 2-ketogluconate (2-KG). We recently demonstrated that a P. aeruginosa mutant lacking the 2-KG transporter KguT is less virulent than its kguT+ parental strain in an insect infection model, pointing to 2-KG branch of glucose utilization as a possible target for anti- Pseudomonas drugs. In this work, we devised an experimental protocol to find specific inhibitors of the 2-KG pathway of P. aeruginosa glucose utilization and applied it to the screening of the Prestwick chemical library. By exploiting mutants lacking genes involved in the transport of glucose derivatives in the primary screening and in the secondary assays, we could identify sanguinarine as an inhibitor of 2-KG utilization. We also demonstrated that sanguinarine does not prevent 2-KG formation by gluconate oxidation or its transport, suggesting that either KguD or KguK is the target of sanguinarine in P. aeruginosa.